Acceptance and commitment therapy: history, foundations, model and evidence (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
The objective of this study is to present a historical and conceptual review of Acceptance and Commitment Therapy (ACT). It is a cognitive-behavioral therapy based (a) on functional contextualism, a philosophy aiming to predict and influence behavior with precision, scope, and depth, and (b) on relational frame theory, a post-skinnerian approach of language and cognition. ACT proposes a model of behavior change, psychological flexibility, which explains healthy and psychopathological functioning through interaction of normal psychological processes. Process and effectiveness research evidence signal that ACT is a promising therapeutic approach openly guided to identify human behavior mechanisms of change.
Keywords: acceptance and commitment therapy; functional contextualism; relational frame theory; psycho-logical flexibility; cognitive-behavioral therapy